Generation and propagation of ion cyclotron waves in nonuniform magnetic field: Application to the corona and solar wind. Issue 11 (28th November 2014) - Omidi, N.; Russell, C. T.; Jian, L. K.; Isenberg, P.; Wei, H. Y.
Abstract With the objective to understand the generation, propagation, and nonlinear evolution of ion cyclotron waves (ICWs) in the corona and solar wind, we use electromagnetic hybrid (kinetic ions and fluid electrons) simulations with a nonuniform magnetic field. ICWs are generated by the temperature anisotropy of O5+ ions as minority species in a proton‐electron plasma with uniform density. A number of magnetic field models are used including radial and spiral with field strength decreasing linearly or with the square of the radial distance. O5+ ions with perpendicular temperature larger than parallel are initially placed in the high‐magnetic field regions. These ions are found to expand outward along the magnetic field. Associated with this expansion, ion cyclotron waves propagating along the magnetic field are also seen to expand outward. These waves are generated at frequencies below the local gyrofrequency of O5+ ions propagating parallel and antiparallel to the magnetic field. Through analysis of the simulation results we demonstrate that wave generation and absorption take place at all radial distances. Comparing the simulation results to observations of ICWs in the solar wind shows some of the observed wave characteristics may be explained by the mechanism discussed in this paper.